Implementation and evaluation of a model-based risk management process and service enhancement for home-based community care services amidst COVID-19 pandemic in Hong Kong: A mixed-method approach - Yang, Caroline W. L.; Wan, Alice N. T.; Kwok, Mable C. W.; Lam, Tai-Hing; Lai, Agnes Y. K. (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic has greatly challenged all public social services, particularly home-based community care services (HBCCS). Aberdeen Kai-fong Association (AKA) is a non-government organization (NGO) in Hong Kong that systematically manages the challenges to HBCCS. This paper presents a practical example of the implementation and evaluation of the risk management process for HBCCS. Methods Mixed-method design was used to evaluate the implementation of the risk management process in encountering the challenges from existing and potential problems to maintain and enhance HBCCS in four major areas amidst the pandemic. A cross-sectional questionnaire survey and three qualitative focus group interviews were conducted by AKA from 30 December 2021 to 12 March 2022 to collect staff feedback on the institutional risk management process in four areas. Results 109 HBCCS staff members (69% aged 40 years or above; 80% female) completed the questionnaire survey. For resource arrangement and staff training, over 90% of the participants agreed (including strongly agreed) that they had sufficient and reliable personal protective equipment and clear infection control guideline and effective training. Over 80% agreed they had safe working space and effective manpower allocation. However, only 75% agreed they had received emotional support from the organization. Over 90% agreed that the basic services were maintained for service continuation and enhancement, the service users and their families trusted the organization, and the provided services were adjusted according to users' needs. 88% agreed that the organization had obtained support from the neighborhood. For communication among stakeholders, over 80% agreed they had open discussions with the senior management team, and the senior management team was willing to listen. Twenty-six staff members joined the three focus group interviews. The qualitative findings corroborated the quantitative results. Staff appreciated the organisation's work to enhance staff safety and continue advancing services during this difficult period. Regular in-service training, updated information and guidelines to staff, and proactive phone calls to service users, especially the elderly, were suggested to enhance the quality of services. Conclusions The paper could help NGOs and others encountering management challenges in community social services in diverse settings amidst the pandemic and beyond.